Expert judgment in project management : narrowing the theory-practice gap - Szwed, Paul S. (Project Management Institute, 2016)
From the publisher: Expert judgment is a major source of information in almost every industry today. Experts can help project managers ensure that their projects are completed successfully, on time, and on budget. In some cases, their input can be vital. Too often, however, companies lack detailed processes for finding and consulting with experts, which can make it hard not only to choose the right expert but to match his or her expertise to the project at hand. In Expert Judgment in Project Management: Narrowing the Theory-Practice Gap, author Paul S. Szwed offers research that will help project managers become more adept at using expert judgment effectively. The study begins by exploring the use of expert judgment in several fields outside of project management, including engineering, environmental management, medicine, political science, and space exploration. Then, it takes a look at the underdeveloped and informal state of expert judgment as it currently exists in project management. By highlighting the gaps between how project management and other fields utilize experts, Szwed is able to make several critical recommendations. His suggestions may help project managers improve the way they select, train, and work with experts so they can choose the right experts for the right projects, and make the most of expert judgment to increase the odds of any project's success.